The Process of freezing skipjack tuna (Katsuwonus Pelamis) in CV. Novira Abadi - Talcha Aqilla; Nanda Rizki Purnama; Adli Waliul Perdana; Nurfadillah Nurfadillah; Irwan Irwan; Ratna Mutia Aprilla; Moh. Johan Efendi (Universitas Syiah Kuala, 2023)
Skipjack tuna is one of the marine products that is often consumed by the community. Skipjack tuna with good quality requires special handling, namely the fish freezing method. Freezing skipjack tuna aims to maintain the quality and freshness of the fish in the long term. The freezing process can inhibit bacterial growth, enzyme activity or oxygen oxidation which causes quality deterioration (decay) and causes damage to fish. The purpose of this field work practice service is to find out the process of freezing skipjack tuna (Katsuwonus pelamis) which is carried out at CV. Novira Abadi Banda Aceh. The method used is a participatory method, observation, interviews, and documentation by following directly in the frozen fish processing process. The results of the service showed that the freezing process of skipjack tuna carried out at CV. Novira Abadi consists of several stages, namely receiving raw materials, washing I, sorting, weighing, washing II, preparation in pans, labeling I, freezing, unloading, packaging and packing, labeling II, storing in cold storage, and stuffing.Keywords: Freezing, Skipjack Tuna, Fish Freshness, Quality